2013
DOI: 10.3109/14756366.2012.750311
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase inhibitory properties of novel sulfonamide derivatives of aminoindanes and aminotetralins

Abstract: Six sulfonamides derived from indanes and tetralines were synthesized. The human carbonic anhydrase isozymes hCA I and hCA II inhibition effects of the synthesized sulfonamides were determined. From these compounds, while N-(5,6-dimethoxy-2,3-dihydro-1H-inden-2-yl) methane sulfonamide showed the most potent inhibitory effect against hCA I (K i ¼ 46 AE 5.4 mM, r 2 ¼ 0.978), N-(1,2,3,4-tetrahydronaphthalene-2-yl)methanesulfonamide was found to have the best inhibitory effect against hCA II (K i ¼ 94 AE 7.6 mM, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 46 publications
1
66
0
Order By: Relevance
“…It was reported that phenolic compounds act as CAIs 62,67,70,71 by binding to CA in a diverse manner compared to the classical CAIs, which coordinate the Zn 2+ ion in the active site of the enzyme by substituting a water molecule or hydroxide ion for the fourth, non-protein ligand 67,72 . X-ray crystallography studies from Christianson's group showed the inhibitor to be anchored by means of its -OH moiety to the fourth Zn 2+ ligand by means of a hydrogen bond.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that phenolic compounds act as CAIs 62,67,70,71 by binding to CA in a diverse manner compared to the classical CAIs, which coordinate the Zn 2+ ion in the active site of the enzyme by substituting a water molecule or hydroxide ion for the fourth, non-protein ligand 67,72 . X-ray crystallography studies from Christianson's group showed the inhibitor to be anchored by means of its -OH moiety to the fourth Zn 2+ ligand by means of a hydrogen bond.…”
Section: Resultsmentioning
confidence: 99%
“…a-CAs are among the most effective catalysts known in nature. The a-CAs are present in vertebrates, algae, protozoa, and cytoplasm compartment of green plants, as well as in some bacteria [27][28][29][30][31][32] . In humans, a-CAs are diffused in different tissues including the blood, kidneys, gastrointestinal tract, reproductive tract, the nervous central system, eyes, skin, lungs, etc.…”
Section: +mentioning
confidence: 99%
“…Both isoenzymes purities were controlled by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) according to Laemmli's method 67 . SDS-PAGE was widely used in biochemistry for separation of biological macromolecule including proteins and enzymes according to their electrophoretic mobility 29 . SDS-PAGE was applied after purification of hCA I, and II isoenzymes.…”
Section: Ca Inhibitionmentioning
confidence: 99%
“…There are sixth main genetic families encoding classes of these enzymes: a-, b-, g-, d-, z-and Z-CAs. It was reported that a-CAs are normally monomers and rarely dimers; b-CAs are dimers, tetramers or octamers; g-CAs are trimers, whereas the d-and z-CAs are less well understood at this moment [26][27][28][29][30] . a-CAs are found in algae, vertebrates, bacteria and cytoplasm of green plants.…”
Section: Introductionmentioning
confidence: 99%